The EUTOS population-based registry: incidence and clinical characteristics of 2904 CML patients in 20 European Countries - Hoffmann, Verena Sophia; Hehlmann, Rüdiger (Leukemia, 2015)
This population-based registry was designed to provide robust and updated information on the characteristics and the epidemiology of chronic myeloid leukemia (CML). All cases of newly diagnosed Philadelphia positive, BCR-ABL1+ CML that occurred in a sample of 92.5 million adults living in 20 European countries, were registered over a median period of 39 months. 94.3% of the 2904 CML patients were diagnosed in chronic phase (CP). Median age was 56 years. 55.5% of patients had comorbidities, mainly cardiovascular (41.9%). High-risk patients were 24.7% by Sokal, 10.8% by EURO, and 11.8% by EUTOS risk scores. The raw incidence increased with age from 0.39/100 000/year in people 20-29 years old to 1.52 in those >70 years old, and showed a maximum of 1.39 in Italy and a minimum of 0.69 in Poland (all countries together: 0.99). The proportion of Sokal and Euro score high-risk patients seen in many countries indicates that trial patients were not a positive selection. Thus from a clinical point of view the results of most trials can be generalized to most countries. The incidences observed among European countries did not differ substantially. The estimated number of new CML cases per year in Europe is about 6370.